Android on Mobile Devices: An Energy Perspective - Paul, Kolin; Kundu, Tapas Kumar (2010 IEEE 10th International Conference on Computer and Information Technology, 2010)
Mobile devices and embedded devices need more processing power but energy consumption should be less to save battery power. Open Handset Alliance (OHA) hosting members like Google, Motorola, HTC etc released an open source platform Android for mobile devices. Android is also used in netbook and embedded platform. Android runs on top of linux kernel with a custom JVM set on top of it. Android uses new power management framework to save power in mobile devices. Android developers are allowed to build only JAVA applications. Google tries to make Android as energy efficient as possible to save battery power in mobile devices. In this work, we present benefits of using Android in low power embedded devices. We compared Android JAVA performance with popular Sun embedded JVM running on top of Angstrom linux. Our work shows that Android provides better VM designs but consumes more energy due to lack of dynamic compiler in Dalvik JVM. The implication is that, Android can become more energy efficient by implementing an optimized dynamic compiler in Dalvik JVM.